Cytoarchitectonic Areas of the Gyrus ambiens in the Human Brain - Ricardo Insausti; Marta Córcoles-Parada; Mar Maria Ubero; Adriana Rodado; Ana Maria Insausti; Mónica Muñoz-López (Frontiers Media S.A., 2019)
The Gyrus ambiens is a gross anatomical prominence in the medial temporal lobe (MTL), associated closely with Brodmann area 34 (BA34). It is formed largely by the medial intermediate subfield of the entorhinal cortex (EC) [Brodmann area 28 (BA28)]. Although the MTL has been widely studied due to its well-known role on memory and spatial information, the anatomical relationship between G. ambiens, BA34, and medial intermediate EC subfield has not been completely defined, in particular whether BA34 is part of the EC or a different type of cortex. In order to clarify this issue, we carried out a detailed analysis of 37 human MTLs, determining the exact location of medial intermediate EC subfield and its extent within the G. ambiens, its cortical thickness, and the histological-MRI correspondence of the G. ambiens with the medial intermediate EC subfield in 10 ex vivo MRI. Our results show that the G. ambiens is limited between two small sulci in the medial aspect of the MTL, which correspond almost perfectly to the extent of the medial intermediate EC subfield, although the rostral and caudal extensions of the G. ambiens may extend to the olfactory (rostrally) and intermediate (caudally) entorhinal subfields. Moreover, the cortical thickness averaged 2.5 mm (1.3 mm for layers I-III and 1 mm for layers V-VI). Moreover, distance among different landmarks visible in the MRI scans which are relevant to the identification of the G. ambiens in MRI are provided. These results suggest that BA34 is a part of the EC that fits best with the medial intermediate subfield. The histological data, together with the ex vivo MRI identification and thickness of these structures may be of use when assessing changes in MRI scans in clinical settings, such as Alzheimer disease.